ДЕМОКРАТИЗАЦИЈАТА НА ЖАНРОВИТЕ ВО МАКЕДОНСКАТА СРЕДНОВЕКОВНА ЛИТЕРАТУРА: (ПРИЧИНА И ОСНОВА ЗА КНИЖЕВЕН РАЗВОЈ) (Filološke pripombe, 2019)
The study is following the process of democratization of genres in Macedonian medieval literature especially from the period in the late Middle Ages. The most typical features of the medieval literature in Macedonia are presented here; an attempt is made to determine the characteristic literary and cultural model. There are certain features evident with the process of democratization in medieval literature: the style of the production of medieval type of literature, the primary literary component of the literature, the expressed diversity of genres in the literary system, and the literary connection with the South Slavic literature as a whole. The procedure of the additional systematization of the literary works is necessary in order to determine the genre development of the medieval Slavic literature. By the application of the procedure a greater overview of the literary works is provided in the specific literary genre frame, as well as their typology based on the specification of their distinctive structural, contextual and functional features. An overview of genres in the old Slavic literature is provided in this study, which emerges from the need to determine the most typical features as a distinctive phase of the specific medieval literary genre in the process of their democratization.